High Density Polyethylene (HDPE) Plastic Waste For Making Paving Blocks Can Improve Environmental Health - Masra, Ferizal (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Waste management is a problem that this nation has never been able to solve. Based on data from Jenna Jambeck (2018), a waste researcher from the University of Georgia, Indonesia is ranked second in the world as a producer of plastic waste, reaching 187.2 million tons after China, which reached 262.9 million tons. The aim of this research is to utilize HDPE (High Density Polyethylene) plastic waste as an additional material for hexagon paving blocks, where the researcher wants to know the savings results from using shredded HDPE plastic waste on sand aggregates in making one paving block and to find out the results of the compressive strength test on Utilization of HDPE (High Density Polyethylene) Plastic Waste as additional material for making Hexagon Model Paving Blocks. This research is a type of experimental research, experimental research or experiment (experimental research) is research by carrying out experimental activities, which aims to determine the symptoms or effects that arise, as a cause and effect of certain treatments or experiments (Notoadmodjo, 2014 ). This research design will use a Completely Randomized Design (CRD) where the variation in the ratio of cement to sand is 1: 6: chopped plastic, 0.45%, 0.5%, 0.55%. The variations in the size of the HDPE plastic pieces were 1 cm and 1.5 cm for each comparison of the number of variations with 3 treatments for each variation in the number of comparisons and variations in the size of the HDPE plastic pieces. The conclusion from this research is that HDPE plastic can be used to make strong paving blocks